Kondisi Terumbu Karang di Perairan Tahua Kecamatan Tidore Utara Kota Tidore Kepulauan - Mahruf Azis; Muhammad Ali Ahmad (Universitas Khairun, 2020)
Coral reef are the most diverse and productive ecosystems. Coral reef ecosystem provide benefits directly to people by providing food, medicines, building materials and other products.Coral reef ecosystems also support others coastal ecosystems which are importantly for human life. This research was conducted at coastal area of Tahua Village of North Tidore Sub-district, Tidore Kepulauan City. Objective of this research is to determine the percentage cover of coral reefs and to assess local community uses of reef at coastal waters of Tahua. Coral data collection was done by applying line transect method or LIT (Line Intercept Transect), conducted at three observation station with 50 meters transects length at three depths, namely 3 meters, 6 meters and 10 meters. Data was analyzed by using Cox formulation. Researh results indicated that coral reef of Tahua has been generally degraded, with live coral cover percentages for three research station measured were of 21.86% at Station I (degraded), 18.87% at Station II (degraded), 27.21% at Station III (fair).